Gamification and older adults: Opportunities for gamification to support health promotion initiatives for older adults in the context of COVID-19 - White, Becky; Martin, Annegret; White, James (2022)
The COVID-19 pandemic has increased reliance on digital service delivery, including the delivery of health promotion initiatives. Health promotion interventions need to carefully consider user engagement. Gamification is a strategy used to engage and motivate people, and evidence shows overall cautious positive results in the use of gamification for older people across a range of health areas although more evidence is needed. Gamification has been used as a strategy in COVID-19 related initiatives and there is potential to build on the evidence to further develop gamification initiatives for those living in the Western Pacific region to impact positively on healthy behaviours and health outcomes.